2012
DOI: 10.1249/mss.0b013e318229d2e9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance, Endurance, and Concurrent Training on TNF-α, IL-6, and CRP

Abstract: Sixteen weeks of RT, ET, or CT in middle-age healthy men has not affected low and moderate IL-6, TNF-α, and CRP levels. CT performed in the same weekly frequency and session duration of ET and RT was effective in increasing both maximal strength and VO2peak, in addition to improvements in lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
4
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 22 publications
13
94
4
8
Order By: Relevance
“…Recently, Bateman et al (22) and Slentz et al (23) found significant changes in body mass and waist circumference after 8 months of training in obese individuals. In contrast, however, others did not find an effect of combined training on these anthropometric variables (37 ns -not significant concerning the impact of combined training on body composition are more consistent. In line with our findings, a decrease in fat mass and an increase in lean body mass after 12 weeks and 8 months of exercise, respectively, were previously reported (23,24).…”
Section: Discussionmentioning
confidence: 78%
“…Recently, Bateman et al (22) and Slentz et al (23) found significant changes in body mass and waist circumference after 8 months of training in obese individuals. In contrast, however, others did not find an effect of combined training on these anthropometric variables (37 ns -not significant concerning the impact of combined training on body composition are more consistent. In line with our findings, a decrease in fat mass and an increase in lean body mass after 12 weeks and 8 months of exercise, respectively, were previously reported (23,24).…”
Section: Discussionmentioning
confidence: 78%
“…A positive effect of resistance training on circulating IL-6 after a single exercise was noted in previously sedentary elderly women and middle-aged men [82,83]. contrarily, no effect of resistance, endurance or concurrent training on IL-6 response to a single exercise session was noted following 16 weeks of training in a group of middle-aged men [84]. Moreover, 12 weeks of aerobic training (five days a week at 50 % of VO 2 max) did not change plasma IL-6 concentrations in obese women despite the decrease in body fat and improvement in insulin sensitivity [85].…”
Section: Il-6 Response To Trainingmentioning
confidence: 88%
“…The test was considered maximum if at least two of the following criteria were met: a) exhaustion or inability to maintain the required speed; b) HR at or above 200 bpm, and c) respiratory exchange ratio (RER) equal to or greater than one. Maximum oxygen consumption (VO 2max) was calculated as described above 22 .…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…In the treatment of obese adolescents, combined exercises has been used with excellent metabolic 20 and inflammatory responses 14 and seems to more effective in improving the visceral fat than aerobic training alone 21 , and induce the same effects in fitness that isolated aerobic and resistance training do 22 . Nevertheless, the impact that the Glu27 allele may have on inflammatory parameters in response to combined training have not been assessed.…”
Section: Introductionmentioning
confidence: 99%